Nerve Stimulator-Guided Brachial Plexus Block Performed in the Amputation of a Calf’s Forelimb - Fernandes, Naftáli Silva; Barbosa, Simone Rodrigues; Carlos de Oliveira, Maria Gláucia; Almeida, Fábio Franco; de Mello Seal, Desirée Coelho; de Moraes, Ugo Monteiro; de Oliveira, Luã Barbalho; Vera de Paula, Valéria (Acta Scientiae Veterinariae, 2019)
Background: Locoregional anesthesia techniques enable the performance of procedures in the distal portion of the limbs, through the parenteral administration of local anesthetic nerve block. There are devices that can increase the effectiveness of these blocks by accurately locating the nerves. These devices include peripheral nerve stimulators, which enable anesthetic to be injected near the plexus, thus reducing the volume of anesthetic required and allowing for the specific blockade of a nerve branch by desensitizing exclusively the area of interest. This paper describes the use of nerve stimulator in the brachial plexus block (BPB) of a calf subjected to amputation of the left foreleg. Case: A newborn calf weighing 30 kg, with a history of injury to the left foreleg, was treated at the Veterinary Hospital of the Federal Rural University of the Semi-Arid Region. Clinical and X-ray examinations revealed a fracture in the medial portion of the metacarpus and radiographic alterations indicative of osteomyelitis, so amputation of the affected limb was recommended. Prior the beginning, during and after the surgical procedure, the animal was submitted to the evaluation of its physiological parameters (heart and respiratory rate, capillary refill time, diastolic, systolic and mean blood pressure and rectal temperature). Because it is a newborn animal, it was decided not to pre-operatively fast. After applying preanesthetic medication (xylazine 0.01 mg/kg IV), anesthesia was induced with ketamine (2 mg/kg IV) and midazolam (0.3 mg/kg IV) and maintained with isoflurane. For the brachial plexus block, 0.4 mL/kg (1.5 mg/kg) of 0.375% bupivacaine was used and aided by a peripheral nerve stimulator to generate 10 mA current, 1 HZ frequency and 100 μs pulse duration, coupled to a nerve stimulation needle, it was possible to observe flexion movements of the limb. The stimulus was decreased until movements were triggered at currents lower than 5 mA and nonexistent at 2 mA, whereupon the anesthetic solution was slowly injected. The blockade promoted anesthesia of the entire distal region of the scapulohumeral joint after 30 min, providing supplemental analgesia throughout the surgical procedure, whose effect persisted up to 6 h after the blockade, thus enabling amputation surgery of the limb. The anesthetic recovery was smooth and without signs of excitation. Post-operatory therapy was dipyrone (25 mg / kg) intravenously (IV), every 12 h for five days, meloxicam (0.5 mg / kg) IV every 24 h for three days; and morphine (0.1 mg / kg) intramuscularly every 6 h for three days. Discussion: The use of nerve stimulation enabled the safe and effective use of BPB in a calf subjected to forelimb amputation surgery. In terms of its analgesic contribution during the intraoperative period, the effectiveness of the blockade was satisfactory, considering that the animal presented no variations in the parameters evaluated during the entire surgical period, when compared to those obtained in the preoperative, and no supplemental analgesic was needed during the surgery. In cattle, BPB is usually performed using a blind approach, using anatomical points as references for its execution, and the anesthesiologist’s experience and skills are a determining factor in the success rate of the technique. Nerve stimulator-guided plexus block is still rarely used in ruminants, and is described experimentally only in sheep, using a technique similar to that employed for dogs, which means this is a pioneering technique in calves. Naftáli Silva Fernandes, Simone Rodrigues Barbosa, Maria Gláucia Carlos de Oliveira, Fábio Franco Almeida, Desirée Coelho de Mello Seal, Ugo Monteiro de Moraes, Luã Barbalho de Macêdo &Valéria Veras de Paula